Love-Based Curriculum Meets Deep Learning: Transforming Islamic Education At SMAN 3 Palembang - Lia Laili Rosadah; Ari Koswara; Yulia Wahyuni; Zuhdiyah (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study aims to analyze the integration of the Love-Based Curriculum (LBC) and the Deep Learning Approach in Islamic Religious Education (PAI) at SMAN 3 Palembang. The LBC emphasizes the cultivation of love, care, and empathy toward God, humanity, the environment, and the nation. Meanwhile, the deep learning approach focuses on meaningful, reflective, and conscious learning processes that encourage students to internalize religious values holistically rather than merely memorizing concepts. This research employed a descriptive qualitative approach with data collected through classroom observations, interviews with Islamic education teachers, and analysis of learning documents. The implementation of the Love-Based Curriculum (LBC) and the Deep Learning Approach in Islamic Religious Education (PAI) at SMAN 3 Palembang has successfully integrated cognitive, affective, and spiritual dimensions in a harmonious manner. The values of love (mahabbah), compassion (rahmah), and brotherhood (ukhuwah) are not only taught theoretically but are also embodied through school culture and real social actions. The synergy between LBC and deep learning fosters a reflective, empathetic, and transformative learning process aligned with the principle of rahmatan lil ‘alamin and the national vision of character education. Although challenges remain, such as limited instructional time and the absence of comprehensive affective assessment tools, this model has proven effective in nurturing learners who are loving, caring, and socially responsible.